Scaling behavior of the quantum phase transition from a quantum-anomalous-Hall insulator to an axion insulator - Xinyu Wu (Nature Communications, 2020)
Understanding the critical scaling behaviors of quantum phase transitions can provide profound physical implications. Here, the authors report temperature dependence of the derivative of longitudinal resistance at a magnetic-field induced quantum phase transition between the quantum anomalous Hall insulator to the axion insulator in magnetic topological insulator sandwich samples.